Be your own brand : achieve more of what you want by being more of who you are - McNally, David, 1946- (BK life book., 2011)
In this second edition of their classic book on personal brand David McNally and Karl Speak show that developing a personal brand is not about constructing a contrived image. Rather, it is a process of discovering who you really are and what you aspire to be. The hallmark insight of this new edition is that the best way to establish a strong and memorable brand is to make a positive difference in the lives of others through making lasting impressions that build trusting relationships. McNally and Speak take you through the process of identifying the key components of your brand, conveying that brand to the world, checking how closely your brand aligns with important relationships in your life?particularly your employer?and assessing your progress along the way. This thoroughly revised and updated edition features new material on how to use social media to build a powerful personal brand and case studies of individuals whose personal brands have changed the world. Squarely delivers where other books have left off by creating a genuine self- understanding and a strong picture of the person you are and want to become to create real sustainable personal change.? --Stephen Weiss, Former President EDMC Online Higher Education and Former President and COO Capella Education Company?A strong personal brand is paramount for effective leadership. Be Your Own Brand is a powerful and practical guide for building deep and meaningful relationships.? --Perry Cantarutti, Senior Vice President, Europe, Middle East, Africa, Delta Air Lines?Be Your Own Brand, when applied within a business organization, has the power to accelerate the pace of organizational brand development tremendously.? --Taras K. Rebet, President, West Europe, Otto Bock HealthCare GmbH?From this book you?ll experience deep introspection and discover your own brand which will surely ignite personal and professional growth.? -- Heather Backstrom, Employee Development Manager, Moog, Inc.? Aircraft Group.